2007
DOI: 10.2310/6650.2007.06032
|View full text |Cite
|
Sign up to set email alerts
|

Future Research in Sex Differences in Obesity and Cardiovascular Disease: Report by the Society for Women's Health Research

Abstract: Obesity has become an international public health concern. In the United States, the rates of overweight and obesity have escalated dramatically in the last several decades. The health implications of obesity stem from its relationship with the development and progression of several health complications and diseases. Cardiovascular disease, which is the number one killer of women and men, is strongly influenced by obesity. The exact biological relationship between these two conditions is difficult to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For example, perceived levels of community violence may strongly impact activity levels of women. 51,52 Burdette et al 51 found that women with young children have higher mean body mass index (BMI; weight / height 2 ) and higher prevalence of obesity as the level of perceived neighborhood safety decreased. Other studies have shown the relationship between neighborhood safety and obesity exists well into later ages.…”
Section: Social Cultural and Environmental Influences On Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, perceived levels of community violence may strongly impact activity levels of women. 51,52 Burdette et al 51 found that women with young children have higher mean body mass index (BMI; weight / height 2 ) and higher prevalence of obesity as the level of perceived neighborhood safety decreased. Other studies have shown the relationship between neighborhood safety and obesity exists well into later ages.…”
Section: Social Cultural and Environmental Influences On Obesitymentioning
confidence: 99%
“…The workshop participants defined the gaps in knowledge and the importance of future research in the basic, clinical, and epidemiological sciences related to obesity. 2 Although attendees focused their discussions on basic and clinical research, such as understanding sex differences in adipose tissue biology and distribution, the participants strongly emphasized the importance of understanding the effects of sex differences in behavior on obesity across the life span.…”
Section: Introductionmentioning
confidence: 99%
“…Although sex differences in obesity and the associated risk of CVD have been known for many years [1,[5][6][7], the mechanism underlying the influence of sex hormones on the development of these pathologies remains poorly understood. The lower prevalence of obesity and diabetes and their associated comorbidities in pre-menopausal women than in age-matched men has been attributed to the protective role of estrogens [1,8].…”
Section: Introductionmentioning
confidence: 99%